PRINCIPLES OF THE JUDICIAL PROCESS AS A MEANS OF PROVIDING QUALITY, RESPONSIBILITY TO JUDGES - Хом’яченко, Світлана Іванівна; Владимиренко, Ігор Вячеславович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: The purpose of the scientific article is to analyze the principles of the court process, assess their compliance with European standards, the practice of the European Court of Human Rights (ECHR). Methods: research and evaluation of the principles (basic principles) of the trial, principles - as system-forming factors. The combination of these features forms the quality of the trial. Results: principles are the basic principles, general requirements for the construction and activity (development) of an object (system), the essential characteristics that are responsible for the proper functioning of the system, without which it would not fulfill its purpose. The combination of the principles of the litigation form, determine its quality. Discussion: in order to provide guarantees to exclude any reasonable doubt as to the impartiality of the court, we believe it is necessary, in our opinion, to proceed to the unification of judicial practice, to introduce (gradually) case law